GAMBARAN KECEMASAN DAN KEPATUHAN REMAJA PUTRI TERHADAP KEBIASAAN BARU PADA MASA PANDEMI COVID-19 DI SURABAYA - Irma Maya Puspita; Annisa' Wigati Rozifa; A’im Matun Nadhiroh (LPPM Universitas Abdurrab, 2021)
The COVID-19 pandemic outbreak threatens not only physical health, but also the psychological health of society. Psychological effects have mild to severe impacts. Adolescents are still classified as unstable age, thus they are easily shaken psychologically, experiencing excess anxiety and fear of contracting the virus. Anxiety in adolescents is a natural reaction in this COVID-19 pandemic situation. However, if this situation lasts for a long time, it may cause psychological problems. This study used a descriptive quantitative design with a survey method. Population sampling used non-probability sampling technique, i.e. purposive sampling, in order to obtain a sample of 95 female teenager respondents. This study aims to investigate the anxiety and compliant levels of the female teenager related to new habits during the COVID-19 pandemic. The results showed that the majority of respondents were adolescents with a mild (80%), followed by moderate (8.4%), and severe (10.5%) level of anxiety. Based on these data, it means that teenagers currently have a fairly good level of stress management, although there are still some teenagers who experience severe level of anxiety. The possible cause of this condition was the abundance of information about the corona virus, which had a negative impact. Indeed, we have to update our information as an effort to remain vigilant. However, continuous exposure will have an impact on mental health, in which resulted in stress, anxiety, panic, and fear. Compliant of the female teenagers to new habits during the New Normal period was achieved by washed our hands (61.1%), always using masks (86.3%), always applying social distancing (50.5%), and staying at home (55.8%). The role of adolescents in new habits is urgently needed to prevent transmission of COVID-19.